So Great a Salvation: Biblical Meditations of A Contemporary Desert Father - (3GdCfHG EHjaGfjhS CSba hQFjS OjQ GdbOjS CfHG ebGQs; Pope Tawadros II (3GdHGHG JhGVQhS GdKGfj (B((3JbOje(B)s; El Macari, Wadid; El Makari, Markos; Kaldas, Samuel; Bassilious, Ramza (Egypt The Monastery of St. Macarius (3OjQ GdbOjS CfHG ebGQs, 2019)
"Let those who have been stung by sin and have had its deadly poison spread throughout their body lift their eyes to the One who died once for their sake, Who is now alive and the Life-giver. They shall feel the tremors of a new life running through their inward parts, renewing their thoughts, their affections, their hopes and their desires. The Lord Jesus revealed in His conversation with Nicodemus the mystery of new life which He granted to him and to all who believe in Him; all that remains for us now is to look upon the Lord Jesus in faith. Then, shall we inherit eternal life and taste "so great a salvation" (Heb. 2:3).**THE BOOK IS ENHANCED BY THE FOREWORD BY H.H. POPE TAWADROS II, PATRIARCH OF THE ORTHODOX COPTIC CHURCH.**ANBA EPIPHANIUS (1954-2018) was a bishop of the Coptic Orthodox Church and the abbot of the Monastery of Saint Macarius the Great in Egypt. Disciple of Father Matta el Meskin, he was a tenacious reformer of monasticism, a tireless creator of bridges between the Christian Churches, an internationally respected scholar of biblical, liturgical and patristic texts"--
"Anba Epiphanius, Bishop and Abbot of the Monastery of Saint Macarius the Great (Egypt)"--t.p.
"In appendix, Anba Epiphanius' Apohthegms"-- t.p.
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible